The Powhatan Landscape - Gallivan, Martin D (University Press of Florida, 2024)
Native American history is primarily studied through the lens of European contact, and the story of Virginia's Powhatans traditionally focuses on the English arrival in the Chesapeake. Meanwhile, a deeper indigenous history remains largely unexplored.The Powhatan Landscape breaks new ground by tracing Native placemaking in the Chesapeake from the Algonquian arrival to the Powhatan's clashes with the English. Martin Gallivan details how Virginia Algonquians constructed riverine communities alongside fishing grounds and collective burials and later within horticultural towns. Ceremonial spaces, including earthwork enclosures within the center place of Werowocomoco, gathered people for centuries prior to 1607. Even after the violent ruptures of the colonial era, Native people returned to riverine towns for pilgrimages commemorating the enduring power of place.For today's American Indian communities in the Chesapeake, this reexamination of landscape and history represents a powerful basis from which to contest narratives and policies that have denied their existence.